EFL UNIVERSITY STUDENTS’ DIFFICULTIES IN ACADEMIC WRITING - TIARA K. PASARIBU; ROTUA ELFRIDA (LP2MTBM MAKARIOZ, 2022)
Research on writing skills has been carried out by various researchers in various parts of the world. However, it is still important to reveal the difficulties faced by EFL university students in the practice of academic writing for the balance of lecturers, teachers, and students in overcoming problems in the practice of academic writing. A total of 26 students were involved in this study. They were assigned to write an essay with no less than 250 words with the topic “The Important Role of English in Era 4.0.” This study uses a mixed method. Quantitatively, the data were analyzed to find aspects of errors and the number of errors made by students in their writing. While the qualitative method is used by direct interviews with students to explore the factors of difficulty they face when writing. The findings of this study indicate that students face obstacles in mastering English grammar well before writing practice is carried out. Vocabulary mastery and students' motivation in writing are also considered as the main factor to contribute to the low quality of the students' academic writing.